The Use of Porous Scaffold as a Tumor Model. (11th September 2013) - Zhang, Mei; Boughton, Philip; Rose, Barbara; Lee, C. Soon; Hong, Angela M.
Abstract : Background . Human cancer is a three-dimensional (3D) structure consisting of neighboring cells, extracellular matrix, and blood vessels. It is therefore critical to mimic the cancer cells and their surrounding environment during in vitro study. Our aim was to establish a 3D cancer model using a synthetic composite scaffold. Methods . High-density low-volume seeding was used to promote attachment of a non-small-cell lung cancer cell line (NCI-H460) to scaffolds. Growth patterns in 3D culture were compared with those of monolayers. Immunohistochemistry was conducted to compare the expression of Ki67, CD44, and carbonic anhydrase IX. Results . NCI-H460 readily attached to the scaffold without surface pretreatment at a rate of 35% from a load of 1.5 × 10 6 cells. Most cells grew vertically to form clumps along the surface of the scaffold, and cell morphology resembled tissue origin; 2D cultures exhibited characteristics of adherent epithelial cancer cell lines. Expression patterns of Ki67, CD44, and CA IX varied markedly between 3D and monolayer cultures. Conclusions . The behavior of cancer cells in our 3D model is similar to tumor growth in vivo . This model will provide the basis for future study using 3D cancer culture.